Assessment of Pregnant Women for Information About Hypertension in Pregnancy: A Cross Sectional Study from a Teaching Hospital Outdoor - Rizwana Naz, Bilal Habib, Farukh Bashir, Shoaib Ahmed, Asma Kazi, Sadia Nisar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The term "pregnancy-induced hypertension," or PIH, refers to a pattern of elevated blood pressure that appears during a woman's pregnancy. It is one of the most important factors contributing to the maternal mortality rate and infant morbidity rate worldwide. In addition to its impacts, this risk can be decreased by the transmission of health education that emphasises early identification and appropriate treatment of disease. This study aims to determine the current levels of knowledge about PIH among pregnant women in the general population. Methods: This study was undertaken with the participation of 300 pregnant women, and data were gathered through direct interviews with the participants. The participants' verbal consent to participate in the research was acquired in the form of their acceptance to participate in the study through the use of a questionnaire prepared specifically for the research project. Both the Student T-test and the ANOVA test were utilised in order to explore the parameters associated with pregnancy awareness. Place of Study: Hayat memorial teaching hospital Duration of Study: August 2021 to June 2022 Results: The study shows that 80.6% of pregnant women were aware with the idea of PIH, according to the results of this survey. The first individuals they consulted in order to get knowledge were their friends and family members, followed by medical specialists. As a result of their performance, 47.1% of the participants obtained a score that indicated they had a low level of comprehension. The participants' ages, the type of family they came from, whether or not they had a history of PIH or gestational diabetes, whether or not they participated in sports, and whether or not they attended frequent antenatal care appointments were all important factors in calculating their knowledge score. Conclusions: The outcomes of the study suggested that pregnant participants had a poor understanding of PIH; this underscores the importance of increasing public knowledge and education about the illness. Keywords: Pregnancy induced hypertension (PIH), Preeclampsia